The Capacity for Limb Regeneration During Metamorphosis is Broadly Conserved in the Coccinellidae. (13th August 2020) - Michaud, J P; Nedved, Oldrich; Bayoumy, Mohamed; Abdelwahab, Ahmed; Torres, Jorge; Saxena, Swati; Omkar,; de Santos-Cividanes, Terezinha M; Sakaki, Samane; Rasekh, Arash; Tomoli Torfi, Ebrahim
Abstract: A standardized laboratory procedure tested the limb regeneration abilities of 18 populations (16 species) of lady beetles which were then scored, relative to unoperated controls, based on survival, the proportion regenerating the limb completely or partially, and the magnitude of developmental costs (delayed development, reduced body size) associated with limb ablation. Newly molted fourth instar larvae each had a single foreleg amputated at the base of the femur. All species except Propylea dissecta (Mulsant) showed some complete limb regeneration, with limb regeneration index (LRI) scores ranging from 0.025 to 0.905 out of a possible 1.00 (mean = 0.598). Eriopis connexa Germar, an aphidophagous neotropical species, scored the highest. Widely distributed species that dominate agricultural habitats all scored above 0.75, and the only herbivore, Henosepilachna argus (Geoffroy), scored second from lowest. Prolonged pupal development was the most common cost, occurring in nine species, and correlating negatively with regeneration. Taxonomic distance between species correlated with regeneration, but explained <5% of variation; principal component analysis indicated that the LRI was the main factor distinguishing species. We infer that this capacity is conserved, not because of any adaptive advantage conferred, but because the genes responsible are normally activated during pupal development to generate the adult body plan and reconstitute appendages with direct correspondence to larval progenitors. However, good regeneration capacity was associated with the ecological success of the species. In general, broad geographic distribution, guild dominance, polyphagy, interspecific competitiveness, phenotypic flexibility, and invasiveness were characteristics generally shared by species with high levels of regeneration.